1999
DOI: 10.1002/pc.10362
|View full text |Cite
|
Sign up to set email alerts
|

Uniaxial elongational viscosity of various molten polymer composites

Abstract: Uniaxial elongational viscosity of low density polyethylene (LDPE) that was filled with glass bead, glass flake, talc, or glass fiber was measured. The effect of various inorganic fillers on the strain-hardening property in elongational viscosity was investigated. The strain-hardening property of LDPE became weaker by the addition of fillers in the order of glass bead, glass flake, and talc. Glass fiber filled LDPE showed a strain-softening property. The smaller the particle and the larger the aspect ratio, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 22 publications
(3 reference statements)
5
39
0
Order By: Relevance
“…Finally, the samples were broken after showing necking phenomenon. This decreasing behavior of viscosity agreed with the results reported in the previous paper [4][5][6][7][8][9] and the strain-softening origin seemed to be explained by the idea that undeformed particles generate complex flows around the particles.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Finally, the samples were broken after showing necking phenomenon. This decreasing behavior of viscosity agreed with the results reported in the previous paper [4][5][6][7][8][9] and the strain-softening origin seemed to be explained by the idea that undeformed particles generate complex flows around the particles.…”
Section: Resultssupporting
confidence: 82%
“…Elongational flow behavior of ABS (AcrylonitrileButadiene-Styrene) resins was often reported. [1][2][3] In general, it is known that ABS exhibits a weaker strain-hardening in elongational flow which is similar to that of polymer composite systems [4][5][6][7][8][9] than matrix AS (Acrylonitrile-Styrene Copolymer).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar behaviors were reported for immiscible polymer blends and filler dispersed polymeric systems. [17][18][19] On the contrary, for PS666/SBS(90/10, heat treatment at 260 °C for 60 min), the rupture of sample was not observed. ≧ relaxation at longer times was probably due to the crosslinked SBS having long relaxation times because relaxation modulus curves converged with one another at long times and the tendency became visibly clearer at γ 2.…”
Section: Uniaxial Elongational Flow Behavior Of Sbsmentioning
confidence: 99%
“…The additions of the fillers have never enhanced the strainhardening property of LDPE. 11) We have reported that the unique elongational viscosity property of FEP (tetrafluoroetylene/hexafluoropropylene copolymer) and a small amount of PTFE blend.…”
Section: Introductionmentioning
confidence: 99%